2018
DOI: 10.1002/admt.201800214
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet‐Printed Random Lasers

Abstract: Printing technology has led to a multitude of revolutions in design, conception, fabrication, and application of optoelectronics nowadays especially for wearables and one‐off devices. Recent advances range from solar cells, batteries, sensors, LEDs, displays, biomedical widgets to smart tags. Inkjet‐printed random lasers (IPRLs), demonstrated here, fill in the crucial but missing piece of the puzzle in printed optoelectronics as well as progress in laser research. A broad emission spectrum of IPRL inks coverin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…The extinction spectrum (Figure S9) is comparable with the simulation result of Ag NPs in a PVA environment with a diameter of ∼10 nm. 12,19,21 Standard R6G Solution Synthesis. Sixty milligrams of Rhodamine 6G (R6G) and 0.3 g of PVA were mixed and dissolved in 20 mL of DI water.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extinction spectrum (Figure S9) is comparable with the simulation result of Ag NPs in a PVA environment with a diameter of ∼10 nm. 12,19,21 Standard R6G Solution Synthesis. Sixty milligrams of Rhodamine 6G (R6G) and 0.3 g of PVA were mixed and dissolved in 20 mL of DI water.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The adjective “smart” emphasizes the versatility of this ink, which makes these materials flexible to meet the demands of many purposes, especially the technologies related to optical-encoded systems. Considering the narrow line-width emission spectrum of RLs, this ink is a perfect choice to create wavelength-domain photonics code. ,, Besides, the threshold characteristic requires the excitation power density to be larger than the specified value for achieving the lasing condition, which makes it more difficult to duplicate. These features help in developing a brand new type of security ink that ameliorates the disadvantages of traditional luminescent ink.…”
Section: Introductionmentioning
confidence: 99%
“…In general, almost all of the so-called wet processing techniques can be applied to fabricate random lasers. For example, Liao and coworkers have shown that polymeric random lasers can be easily printed using inkjet printers [ 35 ] or 3D printers [ 36 ]. More bizarre techniques, more suitable for biomaterials processing, can even involve such techniques as cooking.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first theoretical report of Letokhov and experimental breakthrough by Lawandy et al, random lasers have greatly attracted the attention of scientists as a booming laser field. In comparison with regular commercial lasers, the random laser is simpler and less costly to manufacture , and easier to tune. Therefore, it has potential applications in many fields such as imaging, illumination, , sensing, and information technology …”
Section: Introductionmentioning
confidence: 99%